2021
DOI: 10.1021/acs.molpharmaceut.1c00305
|View full text |Cite
|
Sign up to set email alerts
|

[18F]Atorvastatin Pharmacokinetics and Biodistribution in Healthy Female and Male Rats

Abstract: Statins are 3-hydroxy-3-methylglutaryl-coenzyme A reductase inhibitors that are widely used to prevent cardiovascular diseases. However, a series of pleiotropic mechanisms have been associated with statins, particularly with atorvastatin. Therefore, the assessment of [ 18 F]atorvastatin kinetics with positron emission tomography (PET) may elucidate the mechanism of action of statins and the impact of sexual dimorphism, which is one of the most debated interindividual variations influenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…111,112 Transporters influence the pharmacokinetic properties of commonly prescribed drugs, leading to variable exposure of brain tissue. [113][114][115] In assessing CNS drug penetration, a common misconception is that drug presence in cerebrospinal fluid (CSF) is a surrogate for drug levels in brain tissue. As elegantly outlined by Pardridge, 116 a CSF concentration can only be interpreted to reflect drug penetration across the blood-CSF barrier.…”
Section: Transporters: the Next Frontier For Drug Delivery In Strokementioning
confidence: 99%
“…111,112 Transporters influence the pharmacokinetic properties of commonly prescribed drugs, leading to variable exposure of brain tissue. [113][114][115] In assessing CNS drug penetration, a common misconception is that drug presence in cerebrospinal fluid (CSF) is a surrogate for drug levels in brain tissue. As elegantly outlined by Pardridge, 116 a CSF concentration can only be interpreted to reflect drug penetration across the blood-CSF barrier.…”
Section: Transporters: the Next Frontier For Drug Delivery In Strokementioning
confidence: 99%
“…From preclinical data, we know that sex difference influences the finding on PET imaging. For example, preclinical PET studies with [ 18 F]atorvastatin demonstrated faster and higher hepatic uptake and clearance in female compared to male rats, probably due to higher efficiency for exchange between arterial blood and hepatic tissue [1] (Fig. 1).…”
Section: Preclinical Radiopharmacy and Kineticsmentioning
confidence: 99%
“…For example, atorvastatin has demonstrated antioxidant, anti-inflammatory, and anti-apoptotic activities that render it a protective drug against renal injury. However, the pharmacokinetics and biodistribution of atorvastatin in healthy female and male rats indicated that it exhibited an elevated accumulation within the liver (approximately 20-fold the amount in the kidneys), indicative of increased dosage required to achieve renal therapeutic effect [19]. Furthermore, severe liver injury was developed in diabetic rats receiving 20 mg kg −1 atorvastatin, as manifested by diminished liver enzyme activity, elevated bilirubin levels, changes in liver tissue architecture, hepatocyte necrosis, lymphocytic infiltration, and fibrosis.…”
Section: Anti-inflammatory Antioxidantmentioning
confidence: 99%